Efektivitas Pasal 28 Ayat (1) UU ITE tentang Penyebaran Berita Bohong (Hoax) - Firda Laily Mufid; Tioma Roniuli Hariandja (Fakultas Hukum Universitas Islam Jember, 2019)
The presence of the internet can make it easier for humans to obtain, process and present information so that humans are very smooth in carrying out their affairs at the national and international levels, for example in terms of education, culture, kinship, technology, art, commerce, banking, and government. One of the crimes that can be placed on line is the dissemination of false news (hoaxes). Hoax aims to create public opinion, lead opinion, form perceptions, also to have fun that tests the intelligence and accuracy of internet and social media users. . The Hoax case occurred and the spread was so rapid because of the people who easily believed. So that the dissemination of information easier to spread good word of mouth that spread through the media oline like whatsapp and facebook. And one of the villages that will be studied by the researchers is Desa Sanenrejo, Kecamatan Tempurejo, Jember.Keywords: internet, internet crime, hoax